2015
DOI: 10.1038/srep08120
|View full text |Cite
|
Sign up to set email alerts
|

Thermally induced magnetization switching in Fe/MnAs/GaAs(001): selectable magnetic configurations by temperature and field control

Abstract: Spintronic devices currently rely on magnetization control by external magnetic fields or spin-polarized currents. Developing temperature-driven magnetization control has potential for achieving enhanced device functionalities. Recently, there has been much interest in thermally induced magnetisation switching (TIMS), where the temperature control of intrinsic material properties drives a deterministic switching without applying external fields. TIMS, mainly investigated in rare-earth–transition-metal ferrimag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 43 publications
(71 reference statements)
1
22
0
Order By: Relevance
“…At low temperatures (T < 10 °C), the Fe coercive field (58 Oe) is about twice that of α-MnAs (27 Oe), confirming that no (or very weak) coupling exists between the two ferromagnetic layers. For this specific sample, we also confirmed that MFe can be reversed by thermal cycling [13]. As mentioned above, by working in T-MOKE geometry one can improve considerably the magnetic asymmetry ratio with respect to employing circular polarization (Figure 1d).…”
Section: Magnetic Response Of the Fe Layersupporting
confidence: 61%
See 4 more Smart Citations
“…At low temperatures (T < 10 °C), the Fe coercive field (58 Oe) is about twice that of α-MnAs (27 Oe), confirming that no (or very weak) coupling exists between the two ferromagnetic layers. For this specific sample, we also confirmed that MFe can be reversed by thermal cycling [13]. As mentioned above, by working in T-MOKE geometry one can improve considerably the magnetic asymmetry ratio with respect to employing circular polarization (Figure 1d).…”
Section: Magnetic Response Of the Fe Layersupporting
confidence: 61%
“…Although a laser pulse is the external stimulus that promotes the magnetization reversal, here the underlying physics is rather different from the all-optical switching processes reported in the literature [15][16][17]. As for the static case [13], the laser-induced switching in Fe/MnAs is driven by the appearance and disappearance of surface dipolar fields, and its speed is determined by the timescales of the MnAs structural modifications in response to the external stimulus.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations